Islam and International Standards of Human Rights: An Analysis of Domestic Implementation of International Human Rights in Islamic Culture - Hussain, Nazar; Xi, Wu; Saifullah, Saifullah; Shumaila, Shumaila (CV. BImbingan Belajar Assyfa, 2023)
The understanding of human rights concepts and laws has developed dramatically. Human rights concepts have shaped the moral, ethical, legal, political, and religious realities of many civilized nations. Modern nations give utmost significance to humans, and all laws of the states revolve around humans. Murder, terrorism, honor killing, and the denial of human rights are frequently blamed on Islam. This review paper focused on the practical conditions of human rights in Pakistan as an Islamic country, based on human rights reports and observations, and its relevance to the contemporary discourse on human rights within international standards of human rights. Islam advocates the peaceful co-existence of peoples, religions, and societies and guarantees individual and collective rights. Rather, human rights are a central feature of Islam. Islam as a religion recognizes two types of rights: rights that humans are obliged, by virtue of being the creations of God, to fulfill and obey, and rights that they are entitled to expect from their fellow human beings. Domestic implementation failure of human rights refers to moral collapse and state failure